1991
DOI: 10.1063/1.347734
|View full text |Cite
|
Sign up to set email alerts
|

Study of the optical transitions in electrodeposited CuInSe2 thin films

Abstract: Optical absorption coefficients of electrodeposited CuInSe, thin films were determined from the measured transmittance and reflectance at normal incidence of light in the wavelength range 400 to 2000 nm. As-deposited CuInSe, is found to be a direct-gap semiconductor with an allowed direct transition whose gap energy is Ega = 0.96 eV and a forbidden direct transition whose gap energy is Egf = 1.38 eV. After heat treatment of the films at 400 "C, a decrease in the optical absorption was observed at energies belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…3. The band gap of the nanotube arrays was determined to be 1.04 eV which corroborates very well with the observed CISe band gap energies at room temperature as reported in literature 54,59,60 .…”
Section: Resultssupporting
confidence: 90%
“…3. The band gap of the nanotube arrays was determined to be 1.04 eV which corroborates very well with the observed CISe band gap energies at room temperature as reported in literature 54,59,60 .…”
Section: Resultssupporting
confidence: 90%
“…It has been reported that ZnS is a direct band gap semiconductor and therefore plots of ( Ah ν) 2 versus h ν should be straight lines with intercepts on the energy axis giving the band gaps of the films . Such a plot for ZnS thin films electrodeposited at various times is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…3, the band gap decreased with an increase of the deposition time. It has been reported that Sb 2 Te 3 is a compound-semiconductor with a indirect band gap and therefore, the plots of (ahm) 2 versus hm should be a straight line and intercepts on energy axis would give the band gap of the film [29]. The band gaps of electrodeposited Sb 2 Te 3 thin films for 35 and 10 min were found to be 0.29 and 0.46 eV, respectively.…”
Section: Electronic Properties Of Sb 2 Te 3 Nanofilmsmentioning
confidence: 97%